Analytical modeling of the human cardiovascular system with real-time implementation using NI ELVIS-II - Chettri, Sisir; Kumar Bhoi, Akash; Soo Chae, Gyoo; Gurung, Nilas; Sharma, Ashis (International Journal of Engineering and Technology, 2018)
Cardiovascular System, which consists of the heart, the systematic circulation and the pulmonary circulation is said to be the transport system for the human body. Modeling of cardiovascular system has become important for clinical researchers and for deeper understanding of blood circulation in the human body. This paper uses the lumped method which is also known as an electrical analogy for modeling and simulation of human cardiovascular system. A simplified complete lumped parameter model of the Human Cardiovascular System has been developed with real time implementation focusing mainly on blood flows. A resistor, an inductor and a capacitor are used to model every blood vessel, ventricles, atrium and set of all veins and capillaries. A pulse generating circuit is also modeled which acts as a power supply for the heart that controls the contraction of heart muscles.Â Â Â
Keywords: Lumped Parameter; Electrical Analogy; Cardiovascular System; NI ELVIS II; Sinoatrial Node Pulse Generator; Blood Circulation